Clinico-Pathological Spectrum of Laryngeal Lesions Over Seven years ina Tertiary Hospital - Sohaila Fatima; Rabab Nasir Mohamed Badr; Bouvier Francis Valere D’sa; Wajih Ahmed Siddiqui; Nihal Ibrahim Mirza (Tropical Journal of Pathology and Microbiology, 2022)
A 38yr old male was incidentally detected to have chronic liver disease with portal hypertension. Hegives a family history of liver disease. On complete workup, the arsenic levels in his family memberswere found to be high. His liver biopsy showed features of Hepatoportal sclerosis. Two years later,his liver imaging showed a suspicious nodule in the Right lobe, following which he underwent a livedonor liver transplant. Histopathology of the explanted liver revealed, areas of cavernoushemangioma, epithelioid hemangioendothelioma with a focus of diffusely infiltrating Angiosarcoma,in a background of Hepatoportal sclerosis.